Both introduced and extinct: the fallow deer of Roman Mallorca - Valenzuela, Alejandro; Baker, Karis; Carden, Ruth F.; Evans, Jane; Higham, Thomas; Hoelzel, A. Rus; Lamb, Angela L.; Madgwick, Richard; Miller, Holly; Alcover, Josep Antoni; Cau, Miguel Ángel; Sykes, Naomi (Elsevier, 2016)
The archaeological record concerning the distribution and timing of fallow deer translocation across the Mediterranean has been growing in the last years. This knowledge has provided important insights into the movement, trade patterns and ideology of past societies. Unfortunately, the dispersal of fallow deer to the western part of the Mediterranean is insufficiently understood. To fill this gap, this article presents the results of a multidisciplinary investigation (combining the zooarchaeological evidence with AMS radiocarbon dating, isotope analyses and preliminary aDNA results) from a set of remains recovered from archaeological sites on Mallorca (Balearic Islands, Western Mediterranean). The purpose is to explore the timing, circumstances and meaning of the fallow deer's introduction to this island, as well as their subsequent management and extirpation. The results of these proxies confirm the arrival of the fallow deer during the Roman period and, after a short expansion with the establishment of vivaria, its disappearance after the Byzantine period.